Prime Mates: The Simian, Maternity and Abjection in Brobdingnag. (25th June 2020) - Chow, Jeremy
Abstract: This article investigates the layered nature of animality, maternity and abjection epitomised by Gulliver's frightening adventures in Brobdingnag. I focus specifically on the maternal force‐feeding that Gulliver is subjected to by the Brobdingnagian monkey, which he describes as 'the greatest Danger I ever faced in the Kingdom'. The monkey is killed following the episode, which temporarily restores Gulliver's stalwart sense of self. I contend that the monkey incident in Brobdingnag decentres Gulliver's sense of identity and demonstrates the violability of his body by the feminised animal, which ultimately destabilises his sense of masculinity and opens myriad queer potentialities.